Identification and Classification of the Unique Features of Mass Housing Projects. (23rd October 2014) - Kwofie, Titus Ebenezer; Fugar, Frank; Adinyira, Emmanuel; Ahadzie, Divine Kwaku
Abstract : Mass housing projects (MHPs) are said to differ significantly from the "one-off" traditional building projects often encountered in the construction industry and thus require unique management skills and approach in MHPs delivery. This unique nature of MHPs contributes to managerial inefficiencies that result in delivery failures when management approaches are not adapted to the project characteristics. However, understanding and knowledge of the unique attributes of MHPs are critical towards improving the organisation, planning, managerial effectiveness, and delivery success of mass housing projects. To date, extensive studies establishing the unique features of mass housing projects are lacking. This study is set out to identify what constitutes the unique features of mass housing projects by comparing mass housing projects to traditional "one-off" building projects. A questionnaire survey was used to establish mass housing practitioners' perception of the unique characteristics of MHPs. Data analysis involving mean scores and ANOVA revealed 10 unique features of MHP. A clear and systematic understanding of these unique features of MHPs is crucial for evolving effective project management practices and critical competencies towards successful delivery of current and future MHPs.